Results of Frontalis Suspension Surgery in Eyes with Poor Levator Muscle Function - Onur Yaya; Nedime Demir Deveci; Ayşe Feyza Önder (Haseki Tıp Bülteni, 2015)
Aim: To evaluate the results of frontal suspension surgery with autologous fascia lata or silicon rod. Methods: We retrospectively evaluated the results and the complications of frontalis suspension surgery performed in patients with levator muscle function ≤5 mm, who presented with the complaint of ptosis. In patients operated unilaterally, the success of the surgery was graded according the difference between eyelid heights: a difference of <1 mm was considered successful, 1-2 mm - satisfactory, and a difference of >2 mm was accepted as unsuccessful. In those who were operated bilaterally, the success of the surgery was graded according the upper eyelid level: an eyelid level 0-3 mm below the limbus was recorded as successful, >3 mm below the limbus with an open optic axis - satisfactory, and occluded axis was considered unsuccessful. Results: Seventeen eyes of 14 patients enrolled in the study. Silicon rod was used in 9 eyes and autogenous fascia lata was used in 8 eyes. Surgical outcome was recorded as successful in 9 eyes, as satisfactory in 4 eyes and as unsuccessful in 4 eyes. In eyes with unsuccessful outcome, revision surgery was performed within 10 days after surgery. Punctate keratopathy (5 eyes), lagophthalmos (1 eye), mild undercorrection in the temporal side of the eyelid (1 eye) and severe upper eyelid edema (1 eye) were recorded as complications. One patient who was operated with autologous fascia lata complained of leg pain in donor site and, in one patient, incision dehiscence needed to be repaired. Conclusion: Surgical success after primary and revision surgeries were rated as successful in 13 of 17 eyes (76.47%) and as satisfactory in 4 of 17 eyes (23.53%). (The Medical Bulletin of Haseki 2015; 53:36-40)